Unlocking Learners' Potential through Project-Based Learning: Factors Influencing Students’ Engagement in the EFL Classes - Hind Maalfi; Amar Faryat; Hind Brigui (Yayasan Visi Intan Permata, 2025)
Engagement is widely recognized as a key factor in the success of the learning process. Project-based Learning (PjBL) seems to stand out as an approach promoting this factor. This qualitative case study explores how students engage in the PjBL classroom and investigates the key factors influencing students' engagement. This study used a convenience sampling method and took common core students as its population. Participants were taught through PjBL for 8 weeks. Data were collected through field observations during the implementation, and semi-structured interviews after the implementation. Data were analyzed using thematic analysis. Findings reveal considerable levels of students' behavioral, cognitive, emotional, agentic, and social engagement in the PjBL classroom. This paper also determined interest, collaboration, group dynamics, voice and choice, desire for achievement, and instructor support, as factors that enhance students' engagement. This approach is found to foster a supportive learning environment conducive to learning. Given its advantages, it deserves more attention from curriculum designers.